Migration Labor Laws - Pitukhina, Maria (European Journal of Social Science Education and Research, 2022)
This study continues to discuss the various legislative structures associated with migrant workers 'unfree labor;' as it also continues to question as to how a set of laws and standards regarding international labor will articulate and justify this problem adequately and would then attempt to fix it. The study continually relates to the exploitative, enforced labor activities, involving slavery, debt slavery, forced labor and trading in labor. A "labor -based framework" could possibly be regarded as an empirical paradigm that takes into account the political and economic history of exploitation; emphasizes on the deterrence and social explanations for inequality and abuse rather than on the enforcement of slavery; recognizes the value of labor rights and other labor market regulatory frameworks and considers the progression of spectrum within these regards.
Keywords: Migration Labor Laws